Monument : Art and Vulgarity in Saddam Hussein's Iraq. - Makiya, Kanan (I.B. Tauris, 2003)
In Baghdad, an enormous monument nearly twice the size of the Arc de Triomphe towers over the city. Two huge forearms emerge from the ground, clutching two swords that clash overhead. Those arms are enlarged casts of those of Saddam Hussein, showing every bump and follicle. The 'Victory Arch' celebrates a victory over Iran (in their 8-year long war) that never happened._x000D__x000D_'The Monument' is a study of the interplay between art and politics - of how culture, normally an unquestioned good, can play into the hands of power with devastating effects. Kanan Makiya uses the culture invented.